Analisis Penerapan Sistem Pengendalian Internal Pengeluaran Kas pada Hotel - Purba, Florensia Deviana; Utama, I Made Karya (E-Jurnal Akuntansi; Vol 33 No 5 (2023)DO - 10.24843/EJA.2023.v33.i05.p13, 2023)
The aim of this research is to analyze the implementation of the cash disbursement internal control system with a focus on purchasing activities at the Ramada By Wyndham Bali Sunset Road Kuta Hotel. The analysis was carried out using a descriptive method. The results show that the internal control system for cash disbursements for purchases has been running quite well starting from the organizational structure, authorization system and recording procedures, sound practices and employee quality. However, there are doubles made for cash holders and petty cash holders as well as in the purchasing and receiving departments Keywords: Internal Control System; Cash Disbursement; Purchase